STRATEGI PEMENUHAN KEBUTUHAN INDUSTRI PENGOLAHAN IKAN DI PELABUHAN PERIKANAN SAMUDERA BELAWAN - Muhammad Reza; Tri Wiji Nurani; Iin Solihin (Jurnal Teknologi Perikanan dan Kelautan, 2019)
The ocean fishing port of Belawan is the development center of the fish processing industry and fishing center in the North Sumatra Province. There were 25 fish processing industries in the Ocean fishing port of Belawan. The need for raw material of the fish processing industry increase per year, but the need is not fulfilled by the continuity supply. The objectives of this study were to estimate the needs of raw materials for the fish processing industry, to identify the origin of raw materials for fish processing industry and estimate the availability of raw materials, to formulize strategies for the fulfillment of raw materials of the fish processing industry. The collecting data method used were observation and interview method. Then, the data analysis used was descriptive and SWOT analysis. The result showed that the needs of raw materials for fish processing industry was 85.714 ton/year. While, the fish origin in the ocean fishing port of Belawan were from fish landed inside the fishing port and outside fishing port (Aceh, Bengkulu, Padang, Batubara, and Tanjung Balai). Then, the supply estimation (operational capacity) was 54.429 tons/year. The level of need supplying of fish processing industry was 63%. Based on the SWOT analysis, the strategies to supply the need of fish processing industry were developing the port facilities (cold storage) and utilization of human resources, making collaboration with related stakeholder to support the supply and price of raw material in stable condition, conducting law enforcement through individual that obstruct the raw material to industry.